Gambaran Kualitas Hidup Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa di RSA Bandar Lampung - Gresya Linda Siregar; Evelyn Hemme Tambunan (NHM PRESS, 2023)
The kidney is a very important organ in regulating the body's fluid and electrolyte balance. If the kidneys are damaged, chronic kidney disease occurs which causes the need for renal replacement therapy, namely hemodialysis. The hemodialysis therapy may affect the quality of life of patients with chronic renal failure. The aim of this study was to determine the description of the quality of life of patients with chronic renal failure who undergo hemodialysis therapy. This study used a quantitative descriptive study with a cross sectional approach. The population in this study amounted to 70 people, and the determination of the sample using convenience sampling technique as many as 57 people. Data collection using the quality of life scale from the World Health Organization Quality of Life (WHOQOL-BREF) which contains 26 items The questionnaire consists of 24 question items covering 4 dimensions, namely physical health, psychological, social and environmental relationships and 2 general question items regarding quality of life. Data analysis in this study used univariate tests. The result showed that the quality of life of chronic renal failure patients undergoing hemodialysis in general is a good majority (81%). While based on the dimensions, the physical health dimension is mostly moderate (51%), the psychological health dimension is mostly good (73.7%), the social relationship dimension is mostly good (66.7%) and the environmental dimension is mostly good (86.0%). The description of the quality of life of chronic renal failure patients undergoing hemodialysis shows moderate and good categories.